Feasibility Study of Proper Filing and Procedure of Services in Clinic at ABC School in Quezon City: Vol.3, No.1B (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
Clinics are very important as they offer treatment and are equipped with medical equipment, which helps in the diagnosis and treatment of many types of diseases. A good and organized filing system is also crucial for clinics, as it ensures the proper filing of patient's medical records and facilitates easy retrieval, contributing to the decreased waiting time for patients.School Health Services are developed on the school grounds to promote the health of students and employees through disease prevention. The clinic services offered by ABC School include Telemedicine and Teleconsult Services, Dental Services, and Medical Services for students and employees.In this Feasibility Study, our team aims to improve the proper filing and procedures of services in the clinic of ABC School. As the school is considering face-to-face classes with limited restrictions, it is essential to be prepared and ensure the safety of every student and employee. Since schools bring together a large number of students and staff, a system must be in place to handle their documents and records[1].The ABC School Clinic is effective in managing the health of its staff and students. However, they struggle with organizing their records, which are currently only available in hard copy, such as book records, folders, and forms. The pandemic has made their work more challenging, as they need to quickly respond to the health needs of those attending the school, ensuring that no one has symptoms of Covid-19 and conducting contact tracing, which requires proper record-keeping.To gather data for this feasibility study, we interviewed the head nurse to learn about their filing system and service procedures, particularly during the pandemic. We also conducted a survey with a few ABC School clinic personnel to understand their issues and address their needs. Keeping these documents for future reference is crucial, as they help in organizing, systematizing, and ensuring efficiency and transparency.In this future state, we propose using an Office Application, such as Excel, to help the clinic trace and find files easily. This will be useful in the present and the future, as Excel has a presentable style, clear and friendly use, and can contribute to the progress of learning and understanding. Additionally, it will help all people who need to access information to do so easily, and everyone who needs to use documents will know where to find them.We also suggest making changes to two services: Medical Services and Dental Services. For Medical Services, we recommend implementing a better medical process to ensure a pleasant experience for everyone and smooth operations. This includes adding a waiting space to facilitate the flow and reduce congestion. As for Dental Services, we propose allowing effective engagement between the patient and dentist to better determine the cause of any toothache.Lastly, we recommend improving the Referral Flowchart to ensure effective communication between the Head Nurse, the hospital, and the patient's relatives/legal guardian. This will help in demonstrating a smooth transaction from gathering patient information to referring them to the hospital. We also suggest keeping all patient information private, with only the parent and the hospital having access. In some instances, the hospital referral transaction may be delayed, and the best approach to solving this is through open and pleasant dialogue.
Keywords: Clinic; Contact Tracing; Covid 19; Feasibility Study; Filing; Flowchart; LGU; Pandemic; Researchers; Services; Encrypted